The use of second-generation web tools in the teaching of materials from the point of view of teachers of private education north of Riyadh - Saudi Arabia - Al Ghamdi, Iman Bint Abdullah; Asiri, Mohammed bin Jaber (Arab Journal for Sciences and Research Publishing, 2016)
The aim of the study was to identify the use of female teachers in the intermediate stage in public schools north of Riyadh for the tools of second generation of internet and aimed to identify the constraints that limit the use of female teachers in the intermediate stage in public schools north of Riyadh for the tools of the second generation of the internet, and see whether or not statistically potential differences in the use of the teachers of the intermediate stage of the tools of the second generation of the internet and are due to the variables of : (specialization and expertise of teaching, the number of courses.). The reseacher used the descriptive approach. The sample included (70) teachers of the intermediate stage of the public education north of Riyadh. The data was collected by means of the questionnaire. The study found a number of results, the most important of which is the use of the second-generation web-based tools in the teaching of subjects in the intermediate stage is at a rare level. Wikipedia is one of the most widely used web tools, and there are technological, social and administrative barriers that prevent the use of the web. The bottom line is that teachers in the above-mentioned school do not use web tools in teaching materials adequately as a result of different factors.